PENGGUNAAN TRAKTOR PERTANIAN UNTUK PENGOLAHAN TANAH DALAM PEMBANGUNAN HTI - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
A study on the use of farming tractor for land tillage in timber estate establishment was conducted at timber estate area of PT Barito Pacific Group in South Sumatra in 1991. The objective was to obtain technical and economic data on land tillage in timber estate using farming tractor. For this purpose, data on productivity, specification, fixed cost and operating cost of ford farming tractor were collected. the resuits were as follows :1. Land tiliage comprized three activities namely.first plowing. second plowing and harrowing.2. Productiitrity in the first plowing ranged between 0.2184 ha/hour and 0. 3048 ha/hour with an average of 0. 2601 ha/hour.3. Operation costs in the first plowing varied from 63.206. -/ha to Rp. 85,027.-/ha with an average of Rp. 71, 782.-/ha.4. Productivity in the second plowing ranged between 0.2100 ha/hour and 0. 3240 ha/hour with an average of 0.2703 ha/hour5. Operation COSIS in the second plowing varied from Rp. 57.315.,-/ha to Rp. 88,428,-/ha withan average of Rp. 69,583.-/ha.6. Tractor productivity in harrowing ranged between 0.3818 ha/hour and 0.5593 ha/hour with an average of 0.4702 ha/hour.7. Costs for harrowing varied from Rp. 34,250.-/ha to Rp. 49,581,-/hq with an average of Rp. 40,647.-/ha8. Average cost of land tillage using ford farming tractor was Rp. 182,012.-/ha.9. it is suggested that soil condition in land tillage be considered to save cost and power.